Prospective associations between childhood social communication processes and adolescent eating disorder symptoms in an epidemiological sample. - Schaumberg, Katherine; Zerwas, Stephanie C.; Bulik, Cynthia M.; Fiorentini, Chiara; Micali, Nadia (European Child & Adolescent Psychiatry, 2021)
Deficits in social cognition and communication, the processes associated with human social behavior and interaction, have been described in individuals with eating disorder psychopathology. The current study examined whether social communication characteristics present in middle childhood (ages 8–14) were associated with eating disorder behaviors, cognitions, and diagnoses across adolescence (ages 14–18) in a large, population-based sample. Participants (N = 4864) were children enrolled in the Avon Longitudinal Study of Parents and Children (ALSPAC), a population-based, prospective study of women and their children. Regression methods tested prospective associations between social functioning using a facial emotion recognition task and parentally reported social communication symptoms (or difficulties), measured by the Social Communication Disorder Checklist (SCDC), with eating disorder symptoms and diagnoses. Misattribution of faces as sad or angry at age 8.5 was associated with purging and anorexia nervosa diagnosis at age 14, respectively, among girls. Furthermore, autistic-like social communication difficulties during middle childhood were associated with bulimia nervosa symptoms during adolescence among both girls and boys. Results did not support global associations between measured social communication deficits and eating disorder risk in this sample, but specific difficulties with facial emotion recognition and social communication may enhance the risk for disordered eating behaviors.